Risk factors for hearing loss associated with hearing alterations in neonates admitted to the Intensive Care Unit of the Hospital Dr. Rafael Ángel Calderón Guardia, San José, Costa Rica, 2018-2019 - Narváez, Amanda María (2022)
Introduction: In Costa Rica, approximately half of the children born annually have risk factors for hearing loss, generating hearing loss of various etiologies that can manifest before, during or after birth. This leads to altered results in neonatal hearing screening tests, such as otoacoustic emissions and automated auditory evoked potentials. Objective: it was proposed to determine the relationship between risk factors for hearing loss and hearing disorders in neonates, based on ICU admission references and the TANU database, between 2018 and 2019, at the Dr. Rafael Ángel Calderón Guardia. Methodology: the research adopted a quantitative approach. Measures of central tendency and dispersion, tests of independence and Pearson's correlation, and a logistic regression model were performed. Results: there is a relationship between risk factors for hearing loss and auditory alterations in screening. Significant factors were found such as anoxia, intrauterine infections, syndromes, malformations associated with hearing loss, ototoxics, stay in the ICU greater than five days, weight less than 1500 g, age in days and intrauterine infections, which predict results of "refer" in screening tests. Conclusions: on the one hand, to carry out an audiological follow-up to neonates who present risk factors for hearing loss, and, on the other hand, to implement improvements in regard to the management of antecedents and hearing tests performed on neonates.